Clot Through the Heart. Issue 4 (July 2015) - Leach, Joseph R.; Elicker, Brett; Yee, Judy; Puppula, Shilpa; Wisneski, Judith A.; Yeh, Benjamin M.
<x xml:space="preserve">Abstract</x> Abstract We present the case of a 67-year-old man with concomitant stroke and pulmonary embolism 1 day after radiofrequency catheter ablation for refractory atrial tachycardia. A chest computed tomographic angiogram revealed "thrombus-in-transit" across a patent foramen ovale, confirming the diagnosis of paradoxical embolism. Paradoxical embolism is a rare definitive diagnosis. Our case is a key demonstration of the even rarer instance where such a diagnosis is confirmed at multidetector computed tomography.